The Cooperative Memorial & Removal Services vs. The Ontario Board of Funeral Services: How A Memorial Society Changed Ontario’s Funeral Industry - Dickey, Eleanor (Ontario History)

(untitled) (The Ontario Historical Society, 2019)
In a test case that the attorney general of Ontario considered of province-wide importance, a small group of citizens in Thunder Bay, who had formed a burial cooperative, took on the province’s funeral industry in the courts in the early 1980s. The resulting judgement fundamentally changed how the industry operated in the province of Ontario.